KEBON JAMBU AL ISLAMY ISLAMIC BOARDING SCHOOL SANTRIPRENEURSHIP DEVELOPMENT STRATEGY THROUGH SOAR ANALYSIS - Nurhadi, Hafidin; Adam, Deden Kurnia; Komala, Euis; Darojat, Jajat; Asyari, Hobir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Today's Islamic boarding schools not only teach classical books as a generational guide but also equip the generation with hard and soft skills to respond to the development of Industry 4.0. The entrepreneur program is a program that creates a generation that has the entrepreneurial character of Islamic boarding school students. This research will present novelty regarding SOAR analysis in evaluating the entrepreneur program at the Kebon Jambu Al Islamy Babakan Ciwaringin Cirebon Islamic Boarding School. This research uses a qualitative method with a Kebon Jambu Al Islamy Islamic Boarding School case study. The data comes from primary data that the researcher took from the Islamic boarding school and secondary data that the researcher took from supporting documents related to the research. From the research results, the Jambu Al Islamy Islamic Boarding School is proliferating, various activities are held in the boarding school environment, and students are given space to work. There is an entrepreneurial contribution in the form of BUMP cooperatives (Islamic boarding school-owned enterprises). Cooperative for basic food and student needs, banking financial institutions, sewing, hydroponic gardens, Jambu Café, LPK Multi-Media. The Kebon Jambu Al Islamy Islamic Boarding School Santripreneur development program shows a very productive and constructive SOAR for Islamic boarding schools, both economically and for Islamic boarding school alums who have soft skills and complex skill competencies.